Multidrug resistance transporters P-gp and BCRP limit the efficacy of ATR inhibitor ceralasertib in cancer cells - Chen, Xuan-Yu; Wu, Zhuo-Xun; Wang, Jing-Quan; Teng, Qiu-Xu; Tang, Hailin; Liu, Qianwen; Chen, Zhe-Sheng; Chen, Wenkuan (Frontiers in Pharmacology, 2024)
The therapeutic effect of chemotherapy and targeted therapy are known to be limited by drug resistance. Substantial evidence has shown that ATP-binding cassette (ABC) transporters P-gp and BCRP are significant contributors to multidrug resistance (MDR) in cancer cells. In this study, we demonstrated that a clinical-staged ATR inhibitor ceralasertib is susceptible to P-gp and BCRPmediated MDR. The drug resistant cancer cells were less sensitive to ceralasertib compared to the parental cells. Moreover, ceralasertib resistance can be reversed by inhibiting the drug efflux activity of P-gp and BCRP. Interestingly, ceralasertib was able to downregulate the level of P-gp but not BCRP, suggesting a potential regulation between ATR signaling and P-gp expression. Furthermore, computational docking analysis predicted high affinities between ceralasertib and the drug-binding sites of P-gp and BCRP. In summary, overexpression of P-gp and BCRP are sufficient to confer cancer cells resistance to ceralasertib, underscoring their role as biomarkers for therapeutic efficacy.